Metal Binding Functions in the Design of Carbonic Anhydrase Inhibitors - Winum, Jean-Yves; Scozzafava, Andrea; Montero, Jean-Louis; Supuran, Claudiu T. (Current Topics in Medicinal Chemistry, 2007)
The carbonic anhydrases (CAs, EC 4.2.1.1) are zinc containing metalloenzymes which catalyse efficiently the reversible hydration of carbon dioxide to bicarbonate with discharge of a proton, playing important physiological and physiopathological functions. To date, 16 different carbonic anhydrase isoforms have been described in higher vertebrates, including humans, and some of them have been considered as important targets for inhibitors with therapeutic applications. The catalytic and structural role of zinc in these enzyme are understood in great detail, and this provided molecular basis for the design of potent inhibitors, some of which possessing important clinical applications mainly as topically acting anti-glaucoma drugs, anticancer or antiobesity agents. The metal binding function is a critically important factor in the development of isozyme-specific and organ-selective inhibitors. Discovery of compounds that possess zinc binding function different from that of the classical one (sulfonamide type) is in constant progress and can offer opportunities for developing novel pharmacological agents. In the present review we will discuss the different zinc binding function reported in the literature up to now in the design of carbonic anhydrase inhibitors.
Keywords: tumors